Accounting for Gender in the Sociology of Childhood: Reflections From Research in Australia and Brazil. (7th April 2015) - Bartholomaeus, Clare; Senkevics, Adriano Souza
The (new) sociology of childhood has contributed much to thinking about childhood as a social construction and recognizing the diversity of childhood(s). However, age and generation are often the primary focus of sources in the field. We argue that attention to gender is rare in the sociology of childhood and, when it is mentioned, is under-theorized. Although there is now a growing amount of feminist research with pre-teen children, there is a lack of discussion between the broad field of feminist studies and the sociology of childhood. In this article, we draw on our own research studies in Brazil and Australia, as well as previous key studies about gender and children, to consider the ways in which gender and age can be conceptualized together, and to demonstrate the significance of gender in children's lives.